Behavioral and neurochemical analysis of ongoing bone cancer pain in rats. Issue 10 (October 2015) - Remeniuk, Bethany; Sukhtankar, Devki; Okun, Alec; Navratilova, Edita; Xie, Jennifer Y.; King, Tamara; Porreca, Frank
Abstract : Abstract: Cancer-induced bone pain is described as dull, aching ongoing pain. Ongoing bone cancer pain was characterized after intratibial injection of breast cancer cells in rats. Cancer produced time-dependent bone remodeling and tactile hypersensitivity but no spontaneous flinching. Conditioned place preference (CPP) and enhanced dopamine (DA) release in the nucleus accumbens (NAc) shell was observed after peripheral nerve block (PNB) selectively in tumor-bearing rats revealing nociceptive-driven ongoing pain. Oral diclofenac reversed tumor-induced tactile hypersensitivity but did not block PNB-induced CPP or NAc DA release. Tumor-induced tactile hypersensitivity, and PNB-induced CPP and NAc DA release, was blocked by prior subcutaneous implantation of a morphine pellet. In sham rats, morphine produced a modest but sustained increase in NAc DA release. In contrast, morphine produced a transient 5-fold higher NAc DA release in tumor bearing rats compared with sham morphine rats. The possibility that this increased NAc DA release reflected the reward of pain relief was tested by irreversible blockade of rostral anterior cingulate cortex (rACC) μ-opioid receptors (MORs). The rACC MOR blockade prevented the morphine-induced transient increased NAc DA release in tumor bearing rats but did not affect morphine-induced effects in sham-operated animals. Consistent with clinical experience, ongoing cancer pain was controlled by morphine but not by a dose of diclofenac that reversed evoked hypersensitivity. Additionally, the intrinsic reward of morphine can be dissociated from the reward of relief of cancer pain by blockade of rACC MOR. This approach allows mechanistic and therapeutic assessment of ongoing cancer pain with likely translation relevance. Abstract : Behavioral and neurochemical analysis of ongoing bone cancer pain demonstrating that the intrinsic reward of morphine can be dissociated from the reward of pain relief.